The effects of resveratrol supplementation on biomarkers of inflammation and oxidative stress among patients with metabolic syndrome and related disorders: a systematic review and meta-analysis of randomized controlled trials. Issue 12 (14th November 2018) - Tabrizi, Reza; Tamtaji, Omid Reza; Lankarani, Kamran B.; Mirhosseini, Naghmeh; Akbari, Maryam; Dadgostar, Ehsan; Peymani, Payam; Asemi, Zatollah
Abstract : The effect of resveratrol supplementation on biomarkers of inflammation and oxidative stress among patients with metabolic syndrome are controversial. Abstract : There are several current trials investigating the effect of resveratrol supplementation on biomarkers of inflammation and oxidative stress among patients with metabolic syndrome (MetS); however, their findings are controversial. This systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted to summarize the existing evidence and collectively determine the effects of resveratrol supplementation on biomarkers of inflammation and oxidative stress among patients with MetS and related disorders. Two authors independently searched electronic databases, including MEDLINE, EMBASE, Cochrane Library, and Web of Science databases, until May 2018 in order to find relevant RCTs. The quality of the selected RCTs was evaluated using the Cochrane Collaboration risk of bias tool. Cochran's Q test and I -square ( I 2 ) statistic were used to determine whether heterogeneity exists across included trials. Standardized mean difference (SMD) and 95% CI between two intervention groups were used to determine pooled effect sizes. Out of 317 potential citations selected based on keywords, 24 RCTs met the inclusion criteria and were eligible for the current meta-analysis. The pooled results obtained by using the random-effects model showed that resveratrol supplementation significantly decreased C-reactive protein (CRP) (SMD = −0.55; 95% CI, −0.84, −0.26; P < 0.001; I 2 : 84.0) and tumor necrosis factor-α (TNF-α) (SMD = −0.68; 95% CI, −1.08, −0.28; P = 0.001; I 2 : 81.3) concentrations among patients with MetS and related disorders. Interleukin 6 (IL-6) (SMD = 0.05; 95% CI, −0.31, 0.41; P = 0.79; I 2 : 85.0) and superoxide dismutase (SOD) (SMD = 0.21; 95% CI, −3.16, 3.59; P = 0.90; I 2 : 97.7) concentrations did not significantly change following resveratrol supplementation. Resveratrol supplementation showed a promising lowering effect on some of the inflammatory markers among patients with MetS and related disorders. Additional prospective studies regarding the effect of resveratrol supplementation on biomarkers of inflammation and oxidative stress by using higher doses of resveratrol and longer duration of supplementation are necessary.